Key catalysts and constraints of urban agriculture for sustainable food systems: A case study of Thiruvananthapuram, India - G S, Sreedaya; S, Smitha; Riza, Mathew; Sheetal, Somashekar Patil; Sreelakshmi, K; Aswathi, Krishna R; Chinchu, V S; Gopika, Somanath; Shalini, J R (Plant Science Today, 2026)
Urban agriculture (UA) has emerged as a key response to the challenges associated with urbanization, addressing urban poverty, food insecurity, livelihood vulnerability and environmental stress. This study examines key catalysts and constraints influencing UA in the Thiruvananthapuram corporation, Kerala, India. Using mixed-methods research design, data were collected from 124 urban farmers across 20 purposively selected wards through pre-tested questionnaires and focus group discussions during 2024. The identified catalysts were categorized into three groups: socio-economic benefits, ecosystem services and fitness and well-being. Analysis revealed significant differences among these three categories, with fitness and well-being emerging as the most influential catalysts, followed by socio-economic benefits and ecosystem services. Psychological well-being and reduction of lifestyle disorders were the primary catalysts, indicating the role of UA in mental and physical health. Socio-economic benefits included improved access to fresh food, income generation and preservation of cultural practices, while ecosystem services contributed to sustainable development, biodiversity and improved environmental quality. The constraints were grouped into institutional and socio-economic categories, with the lack of timely information, extension services and agricultural inputs identified as the major institutional barriers. Socio-economic challenges included poor soil fertility and high costs of specialized inputs and labour. The findings collectively elucidate the key catalytic factors and constraints shaping the adoption and practice of UA.